The impact of financial literacy on finance and economy: A literature review - Bunyamin, Mubarokah; Abdul Wahab, Norwazli (Universiti Malaysia Sabah, 2022)
Financial literacy encourages individuals and society to improve their financial well-being. Hence, increase their capabilities to take part in economic life. This paper aims to investigate the impact of financial literacy on finance and economy. An extensive review of financial literacy literature is carried out, with a specific attention on its correlation with financial and economic aspects. This study unveils that financial literacy gives impacts on personal financial decisions, behaviour, saving and retirement, investment, financial risk tolerance, business, and national economy. This paper will be useful to economists and technologist about the importance of financial literacy with the suggestions on the role of financial technology (FinTech) in enhancing financial literacy, thus financial well-being as well as overall well-being towards industrial revolution 4.0 (IR 4.0).